Perbandingan Model Picture and Picture dan Jigsaw II Meningkatkan Berfikir Tingkat Tinggi - Fajri Arif Wibawa; Edy Purnomo; Darsono Darsono (Jurnal Studi Sosial / Journal of Social Studies, 2017)
The purpose of this study was to find out the effectiveness of high order thinking ability among students who learning using Picture and Picture and Jigsaw II by observing the learning style of students. The research method used was experiment. The result of the research showed that there are differences in students' high-order thinking ability, there are differences in the ability of high-level thinking between students with visual and auditory style, there is interaction between learning model and learning style toward high-level thinking ability, high students thinking ability with Picture and Picture higher in students visual learning style, high-level thinking ability of students with Picture and Picture lower on students whose learning style is auditory, high-order thinking ability of students with higher visual learning style with Picture and Picture, high-level thinking ability of student style visual learning is lower with Jigsaw II.Tujuan penelitian ini untuk mengetahui efektivitas kemampuan berfikir tingkat tinggi antara siswa yang pembelajarannya menggunakan model Picture and Picture dan Jigsaw II dengan memperhatikan gaya belajar siswa. Metode penelitian yang digunakan adalah eksperimen. Hasil penelitian menunjukkan terdapat ada perbedaan kemampuan berfikir tingkat tinggi siswa, ada perbedaan kemampuan berfikir tingkat tinggi antara siswa yang gaya belajarnya visual dan auditori, ada interaksi antara model pembelajaran dengan gaya belajar terhadap kemampuan berfikir tingkat tinggi, kemampuan berfikir tingkat tinggi siswa dengan Picture and Picture lebih tinggi pada siswa gaya belajarnya visual, kemampuan berfikir tingkat tinggi siswa dengan Picture and Picture lebih rendah pada siswa yang gaya belajarnya auditori, kemampuan berfikir tingkat tinggi siswa yang gaya belajarnya visual lebih tinggi dengan model Picture and Picture, kemampuan berfikir tingkat tinggi siswa yang gaya belajarnya visual lebih rendah dengan model Jigsaw II.Kata kunci: berfikir tingkat tinggi, picture and picture, jigsaw II, gaya belajar.